Αγγλικά - Μύθοι Αισώπου: Λεξιλόγιο - Δ'-ΣΤ' Δημοτικού Επ. 66 (Υπουργείο Παιδείας και Θρησκευμάτων, 2020)
: [♪ Μουσική throat singing nur desse Good morning, good morning, good morning! Boys and girls, girls and boys. This is time for English, I am Zafi Zafi Mandali and I teach English, I love my job, but I also love stories and I tell a lot of stories to my students and I've got one story for you today. The story I will tell you and you will understand everything is from Aesop. You think you don't know the word Aesop? What if I tell you Aesopos? Aesopos, exactly. So we're going to be talking about Aesop and Aesop's story. But what do we know about Aesop? Well, we don't know much and we don't know how he looked, but there are some drawings of Aesop. First of all, I want to say that Aesop lived a long, long time ago. He lived in 622 before Christ. Before Christ appeared. Now, that is a long time ago. If we want to know exactly how much time, we have to think of the year we are in. Now, we are in 2020. So if I want to know how old Aesop stories are, I have to add 2020, which is now. With those years before Christ, 620 when Aesop lived. So if I add 2020 with 620, I am going to have 2640 years. That is many years. Another thing we know about Aesop is that Aesop was not a free man. He was a slave. He belonged to somebody. He had a master. We also know that Aesop was not a very good looking man. I mean, he was a bit short. He had a big nose. His back was not straight, but he was such a wise man. He said so wonderful stories, such fantastic stories that everybody listened to him and because they loved his stories, they made him a free man. So he was no longer a slave and as a free man, he continued to tell his stories. Now, Aesop stories are about animals, talking animals. Animals that are like you and me. They have the same needs. They have the same characteristics. And another thing we need to know about Aesop stories is that everybody knows them all over the world. In the whole globe, they know. For example, they read Aesop stories in England, in Italy, in France, in Russia, all over Europe, of course, translated in the language of the country and even in the USA, in Canada, in China, in the whole of Asia and in Africa and in Australia. The whole globe knows about Aesop stories. And do you know why? Do you know why? Well, because Aesop stories tell us great truths. They still teach us things about ourselves. They still send us messages that we need. So, my story is The Peter and the Crown. For the story, I will need some things. Before I start to tell you the story, I will use water. You see the water? It's real. And the water is in a jug. The jug is not full. It's half full. And can you tell me what is it made of? Did you say glass? Yes, that is glass. Perfect. So, another thing, of course, I will need is a pitcher. I love this pitcher. Look at it. It's fantastic. A pitcher has got a handle. You use your hand to hold the handle. And why do we have pitchers? Because we put oil. What else can we put in a pitcher? Oh, you said water. Yes, of course, water. So, water, oil, and you said wine. Of course, wine. And the pitcher, if we look at it, it's got a neck. You see the neck? Like, I've got a neck and you've got a neck. Can you touch your neck? Touch it, right. My neck is long. This is not very long. And then the pitcher has got the body. It's body here. And the body is wide. The neck is narrow. The body is wide. And also it's got its mouth. And its mouth, it's also wide. And one other thing. What is that made of? Is that glass? No, it's not glass. Of course, it's not glass. And of course, it's not wood. You know what? It's metal. Very good. Very, very, very good. Metal. You know what? In Aesop's time, most of the pitchers, they were made from clay. Clay is the soil you get from the earth. And they made fantastic pottery. And if we go to all the museums in Athens and all over the world, we will see ancient pottery. Greek ancient pottery. And the pitchers come in various shapes. So, another thing I'm going to need for my story is a crow. Yeah, I love this crow. I mean, look at it. It's black. And of course, it's a bird. What I like about the crow is that it's total black and it's big. Look at its beak. I mean, we people have noses, yes. But they have beaks. It's something like their nose and their mouth together. So, this is my crow. But you know what? To tell you the story, I don't have a crow with me. I will use my puppet. My lovely puppet. Puppet actually is parrot. It's a parrot. It's not a crow. But my puppet can speak foreign languages. It can speak the language of the crow. Like you can speak English. Of course, Polly is a little bit shy. Polly, will you speak to the kids? Speak to them. But speak in the language of a crow, will you? What's wrong? Oh, no. Don't be shy. They're good. Look at them. They're good children. Come on. Don't be shy. Come on. Listen, listen, listen. You always do this before other kids too. They're good too. Okay, say hello in the language of a crow. Oh, thank you, parrot. Yes, thank you. Thank you for speaking like a crow. Okay, so I think we're ready for our story now. Are you ready for the story? If you're ready, you're going to say yes, yes, yes. You have to say yes, yes, yes and I can hear you because in stories everything happens. Everything is possible. So can I hear you? Yes, yes, yes. Okay, yes, yes. So once upon a time, on a very hot summer day, there was the crow. And the crow was a little bit naughty. It started flying and it flew and it flew and it flew for a long time and it went outside the forest and it got lost. And it was feeling very thirsty. It was feeling thirsty and suffering and he didn't know where to go and find water. I mean, he didn't know where to go. Can you help him? Can you help him? Where can you find water? Because now you know where he is. He's outside a village and he can see some houses but it's a bit late and there isn't anything. There isn't anything. And where can he look for water? Where? Oh, you said in a river. Oh yeah, in a river. Yes, of course, of course. In a river and in a lake you can have a lot of water but you know that place has no river, it has no lake and no ponds and so no, you've got to give him another idea. Oh, you said forest. Oh, but I told you, he's away from the forest and he's thirsty. He needs water now. Where else? You mean outside the houses? Yes, yes, yes, he went, he hopped, he hopped but the houses were closed and there was nobody. What? To go in a supermarket? In a supermarket? Oh, the supermarket, the supermarket, there's no supermarket there. Just a little bit of grocery store but it's late and it's closed. No, you've got to think of something better. Oh, did you say a well? You mean you actually thought of a well? The well, what a good idea. Yes, but poor, poor crow cannot get down in the well because the water is down, down, down, he doesn't know how to get there so he's desperate and he's looking around. And he says I have to find a way and then, and then he sees the pitcher with the water. Gosh, yes, he's going to drink that water so he puts his beak, he puts his beak down but the beak doesn't go down. Oh no, the water is not up, up, up, up so what can he do? He pushes and he pushes, there's no way, there's no way, he needs to think of something and yes, he's crying. Oh no, he sees a rock, he sees a stone and now he's got the idea and he gets hold of the stone and that's very difficult and he carries the stone all the way, all the way and drops it in. Oh no, he needs to find more stones, can you find more stones, can you, can you see more stones? Oh there's more here, yeah here, here, oh gosh, it's hard, it's hard, hard, hard. And where else? There, oh there, yeah you're right, yeah, we have got more here, more here, more here, yes, yes. Oh gosh, no, what does he need? He needs a straw, you mean a straw like the one you have, yes but he doesn't have any straw so now he needs to find more stones and that is a very clever crowd. And he finds a bit more, he tries and he tries and oh yes, he's saved, he's saved and yes and now he's reaching and he's reading and he's so happy, he's solved the problem. And if that water finishes he's going to find more stones and then the water is going to come up but you know what, now our crowd has got its energy and now he's going to fly all the way back to his forest and I think our crowd has learned its lesson. What do you think, what do you think he learned? I think he learned two things, first he learned that he must not fly too far away because he never knows how far he goes, he must not lose his way. And the other thing he knows is that when he has a problem he doesn't give up, he thinks, he thinks and when you think you're going to come up with a solution and that is what he did and that's what we should all do. So that is the story of the crow and the pitcher and that's the end of our story and my children I have a second story for you today. I won't tell you the title of the story, I will tell that at the end. So my story is about a king in a far far land a long long ago and this king was so wise that everybody was happy with him and some people say that he was King Alfonso, others say he was King Akbar, others say he was King Arthur. But the person who told the person who told the person who told me doesn't really remember. So this king was so good and was doing things so wisely that other wise men were coming to his court, to his palace to serve him and to offer him their help. And everybody was happy, his queen was happy, his prince and princesses, his soldiers, his generals, his servants, his wise men, his consultants, the whole population, his consultants, everybody was happy. And some smiled so much from ear to ear that they even hurt. And you know the same king himself was so proud and so happy with himself that he understood that this was not normal. What if, what if something bad happened, what if they lost this happiness, whether there was a change of weather, whether the fields did not give enough crops, enough fruit and what if enemies appeared and there was war, what if illness appeared. He must have a way where he can think calmly and he has to find balance of mind and he didn't know how to do it. So the next day he called his wise people, his wise consultants and he said, my consultants I have a problem and you need to solve that, I don't know how but you have to make a ring that I'm going to wear in the middle finger and this ring is going to have special ability. It must have the ability, I don't know how you are going to do it but it must have the ability to make me calm. If I'm over excited and up in the air, you know, too full of myself, it must bring me down. And when I'm worried, when I'm concerned, when I'm troubled, it must lift me up, it must bring calmness in me. And the wise men looked at each other and they said, your majesty, we have never done this before, we have never heard this before, I don't think, we don't think and the king raised his hand and the wise men realized when the king says something it has to be done and off they went. And they started thinking and they started consulting and they started discussing, arguing, brainstorming, thinking of how to solve the problem. And on the seventh day they thought they found the answer but they wanted to go to the king to ask his approval, so they went to the king, the king received them and the oldest of the wise men said, our king, we think we found the solution but we want your approval because we are not sure if we are doing the right thing. And the king lifted his hand again and said, no, no, you don't need approval, I fully trust you, I'm sure you will do it, off you go. And again they went and one and two and three and four days passed and on the fifth day the wise men came back and the king received them and so the old wise men came forward and he said to the king, your majesty, I think we are ready. And with that he gave him a ring and he gave him a ring and the king looked at the ring and he liked it, it was gold, it even had diamonds, it was quite big and inside there was a message. And as he looked at that message he started changing, his mood changed, he seemed troubled, he seemed a bit worried, he didn't know, he was uncertain and he looked at his wise men and the wise men said, your majesty, what does it say? Read, what does it say? And the king looked at it again, yes, and soon his expression changed, he became calm, he became happy even, satisfied, in control. And he put the ring in his finger and the wise men looked at him and they wanted to know if they had done the thing that the king asked and the king said yes, you did it, congratulations, this ring has got a special quality, it can bring balance in my life. When I'm over excited it can calm me down and when I am worried it can lift me up and with a clear mind I can take clear decisions and I can rule my nation and we are all going to be better. And with that he was happy and the wise men were happy. But my question now is, what was the message in that ring? In class you would have a lot of answers, you would give me different answers, think a little bit more, what can it say, what? I'll tell you, it said this too will pass, four words, this too will pass, but what does that mean? Now at this age I know that I should not be worried about everything because you know life has got its good moments and its difficult moments and we must be prepared for everything. Nothing good lasts forever and nothing bad lasts forever. If for example we have a problem we should know that this too will pass and I think we have a bit of a problem at this time but if we keep our head clean and we can think clearly this too will pass. And with this story my children I say goodbye to you until some other time when we'll say more stories. Bye bye.